1999
DOI: 10.1117/12.367602
|View full text |Cite
|
Sign up to set email alerts
|

<title>High-resolution wavefront control using liquid crystal spatial light modulators</title>

Abstract: Liquid crystal spatial light modulator technology appropriate for high-resolution wavefront control has recently become commercially available. Some of these devices have several hundred thousand controllable degrees of freedom, more than two orders of magnitude greater than the largest conventional deformable mirror. We will present results of experiments to characterize the optical properties of these devices and to utilize them to correct aberrations in an optical system. We will also present application sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The pixel layout and the system configuration of the LCSLM wavefront control report in this work are shown in Figure 1. Operation of LC wavefront controllers has already been demonstrated at low optical power density [1][2][3][4][5][6][7][8]. In this work we addressed the needs of high-energy laser applications.…”
Section: Introductionmentioning
confidence: 96%
“…The pixel layout and the system configuration of the LCSLM wavefront control report in this work are shown in Figure 1. Operation of LC wavefront controllers has already been demonstrated at low optical power density [1][2][3][4][5][6][7][8]. In this work we addressed the needs of high-energy laser applications.…”
Section: Introductionmentioning
confidence: 96%
“…Recent work indicated that liquid crystal light modulator (LCSLM) could be used to replace the deformable mirror to correct wavefront distortions [1][2][3][4][5][6][7][8][9][10][11]. The reflective LC SLM module reported here has a two-inch diameter active aperture with 812 pixels.…”
Section: Introductionmentioning
confidence: 99%